RETRACTED: Gamification from the Viewpoint of Motivational Theory - Karimi, Kianoosh; Nickpayam, Javad (Emerging Science Journal, 2017)
This article has been retracted: please seeÂ Emerging Science Journal policies:(https://ijournalse.org/index.php/ESJ/about/editorialPolicies).Reason: The present article has been retracted at the request of the Editor-in-Chief. This article contains some duplicate material of a paper that was originally published in Gamification in Education and Business, (2014) 21â€“46, doi:10.1007/978-3-319-10208-5_2. One of the conditions of submission of a paper for publication is that authors declare explicitly that all of their work is original and has not appeared in a publication elsewhere. We apologize to readers of the journal that this was not detected during the submission process.